2017
DOI: 10.1088/1757-899x/271/1/012103
|View full text |Cite
|
Sign up to set email alerts
|

Ultimate strength capacity of a square hollow section filled with fibrous foamed concrete

Abstract: Abstract. Concrete-filled sections used as building columns have become popular due to their architectural and structural elements. In recent years, there has been a renewed call for the improvement of materials used as concrete to fill the composite columns. Among these materials, foamed concrete has received great attention due to its structural characteristics and its potential as a construction material used in hollow sections. However, its behaviors as infill material in a hollow section, such as its stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The addition of fibre to the CFHS increases the ultimate load. The inclusion of fibre improves the ultimate load capacity and the deformation and ductility of CFHSs [8,9].…”
Section: Experimental Results and Observationmentioning
confidence: 99%
“…The addition of fibre to the CFHS increases the ultimate load. The inclusion of fibre improves the ultimate load capacity and the deformation and ductility of CFHSs [8,9].…”
Section: Experimental Results and Observationmentioning
confidence: 99%
“…A study by Khairuddin et al [23] on CFHSs using SFs in short columns found that adding rice husk ash (ASH) resulted in good strength and bonding between concrete and SHSs. According to Bhuvaneshwari et al [24] and Jaini, Rum, and Boon [25], using RHA as a sand replacement in FC increased compressive strength due to the high pozzolanic reaction and ability produced by RHA.…”
Section: Fc-filled Hollow Sectionsmentioning
confidence: 99%
“…Meanwhile, SF was added at 0.8% of the total material. The percentage of RHA and SF in the mixture was suggested by Khairuddin et al [23] under the optimal strength of modified concrete. Table 1 shows the mixed design for the FC.…”
Section: Materials Preparationmentioning
confidence: 99%
See 1 more Smart Citation